Collaborative meaning-making using video footage: teachers and researchers analyse children's working theories about friendship. Issue 3 (4th May 2017) - Hedges, Helen; Cooper, Maria
ABSTRACT: Children represent their efforts to make sense of their social worlds in various ways. Having, making and being friends are common foci of children's interactions and identity development. These efforts may become visible through analysing video-recorded snippets of children's play. In particular, repeated viewing of episodes of children's interactions with each other may encourage and prompt adult reflection, analysis, meaning-making, and action. This article reports findings from a qualitative study in Auckland, Aotearoa New Zealand, where children's working theories (thinking) is a key outcome of the early childhood curriculum. We analyse two audiovisual examples of children's thinking (working theories) about friendship and discuss subsequent actions and implications for supporting children's social competence. We argue that research and teaching teams who engage in reflection and dialogue using video footage may create successful learning communities that foster children's working theory development.